TLR or NOD receptor signaling skews monocyte fate decision via distinct mechanisms driven by mTOR and miR-155 - Coillard, Alice; Guyonnet, Léa; De Juan, Alba; Cros, Adeline; Segura, Elodie (Proceedings of the National Academy of Sciences - PNAS, 2021)
Monocytes are rapidly recruited to inflamed tissues where they differentiate into monocyte-derived macrophages (mo-mac) or dendritic cells (mo-DC). At infection sites, monocytes encounter a broad range of microbial motifs. How pathogen recognition impacts monocyte fate decision is unclear. Here, we show, using an in vitro model allowing the simultaneous differentiation of human mo-mac and mo-DC, that viruses promote mo-mac while Mycobacteria favor mo-DC differentiation. Mechanistically, we found that pathogen sensing through toll-like receptor (TLR) ligands increases mo-mac differentiation via mTORC1. By contrast, nucleotide-binding oligomerization domain (NOD) ligands favor mo-DC through the induction of TNF-α secretion and miR-155 expression. We confirmed these results in vivo, in mouse skin and by analyzing transcriptomic data from human individuals. Overall, our findings allow a better understanding of the molecular control of monocyte differentiation and of monocyte plasticity upon pathogen sensing.